2014
DOI: 10.1016/j.ophtha.2013.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Proton Therapy for Uveal Melanoma in 43 Juvenile Patients

Abstract: After PBRT, metastatic and survival rates are significantly better for juvenile than for adult patients with UM. Clinically, juvenile and adult eyes react similarly to PBRT, with patients having a comparable eye retention probability and maintaining a useful level of vision in most cases. This is the largest case-control study of proton therapy in juvenile eyes to date and further validates PBRT as an appropriate conservative treatment for UM in patients younger than 21 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…5,8,17 Those may be the reasons why this group of patients had a higher number of events compared with other studies' reports of lower rates of metastasis. 8,17,18 However, 1 study that found a lower frequency of young patients with posterior uveal melanoma (only 17 of 3207 patients ≤20 years of age [0.5%]) treated with proton beam irradiation showed no deaths or development of metastasis during a long follow-up period (median, 16 [range, 4.7-25.2] years) that was comparable with ours. 18 In our group of patients younger than 21 years, a substantial proportion developed metastasis ( Figure 1) and died of that metastasis ( Figure 2) during available follow-up.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…5,8,17 Those may be the reasons why this group of patients had a higher number of events compared with other studies' reports of lower rates of metastasis. 8,17,18 However, 1 study that found a lower frequency of young patients with posterior uveal melanoma (only 17 of 3207 patients ≤20 years of age [0.5%]) treated with proton beam irradiation showed no deaths or development of metastasis during a long follow-up period (median, 16 [range, 4.7-25.2] years) that was comparable with ours. 18 In our group of patients younger than 21 years, a substantial proportion developed metastasis ( Figure 1) and died of that metastasis ( Figure 2) during available follow-up.…”
Section: Discussionmentioning
confidence: 58%
“…5,8,17,18 Because this was shown by other researchers, the expectation in this analysis was to find a substantially better metastasis and survival outcome in this subgroup compared with older patients, despite the management method used for their PUM. 5,8,17,18 Because we did not find evidence of BAP1 tumor predisposition syndrome and only 1 patient that had oculodermal melanosis, there are only few explanations as to the findings of this analysis compared with other reports. First, because young people who develop a PUM have fewer competing risks for death than elderly persons with the same type of tumor, young people appear to have a higher long-term cumulative probability of death from metastasis than older persons do.…”
Section: Discussionmentioning
confidence: 80%
“…Studies of tumours outside the cns-including skull base chordoma and chondrosarcoma 22,23 , uveal melanoma 23,24 , germ-cell tumours 25 , high-risk neuroblastoma 26,27 , parameningeal rhabdomyosarcoma 28 , bladder and prostate rhabdomyosarcoma 29 , other soft tissue sarcomas 30 , Ewing sarcoma 31 , and mediastinal Hodgkin lymphoma 32 -uniformly showed that pbt is well tolerated, with local control rates similar to or higher than those achieved with photon rt. Although planning studies and early clinical results are promising, long-term data supporting a clear advantage of pbt over photon rt are not yet available.…”
Section: Pediatricsmentioning
confidence: 99%
“…Juvenile uveal melanoma occurring in patients younger than 21 years old is rare, but associated with a significantly favourable survival (Petrovic et al. ). Male gender has been proposed to be associated with increased mortality in patients with uveal melanoma (Virgili et al.…”
Section: Introductionmentioning
confidence: 99%